Does Female Empowerment Promote Economic Development? - Matthias Doepke; Michèle Tertilt (University of Mannheim, Department of Economics, 2014)
Empirical evidence suggests that money in the hands of mothers (as opposed to fathers) increases expenditures on children. From this, should we infer that targeting transfers to women is good economic policy? In this paper, we develop a non-cooperative model of household decision making to answer this question. We show that when women have lower wages than men, they may spend more on children, even when they have exactly the same preferences as their husbands. However, this does not necessarily mean that giving money to women is a good development policy. We show that depending on the nature of the production function, targeting transfers to women may be beneficial or harmful to growth. In particular, such transfers are more likely to be beneficial when human capital, rather than physical capital or land, is the most important factor of production.
urn:nbn:de:bsz:180-madoc-359367
Keywords: 330